Parents Education is One of Affected Factor in Stunted Children Profile in Pekanbaru - Nabillah Nastiti Wardhana; Zahtamal (Sumatera Medical Journal, 2024)
Background: Stunting is a developmental disorder in children caused by poor nutrition, recurrent infections, and inadequate psychosocial stimulation, marked by the child's height or length being below the threshold (Z-Score) of -2 standard deviations. Objective: The aim of this study was to explore prevalence of stunting in Pekanbaru. Methods: This was descriptive research with quantitative data, and the sample size was 75. Results: The family profile of those with stunted children included fathers with mostly secondary education (64%), mothers with secondary education (57.3%), 19 mothers experiencing short stature (CED), with only four mothers receiving additional food, mothers who took iron supplements during pregnancy (80%), children with stunting who were exclusively breastfed (78.7%) and introduced to complementary feeding (80%), children with stunting taken to integrated health posts for regular growth and development monitoring (76%), children with stunting receiving complete immunization (57.3%), families participating in family planning programs (60%), and children with stunting resulting from unwanted pregnancies (40%). Conclusion: The majority of parents with stunted children had a lower to middle education level, low income, did not participate in the national health insurance program (JKN), and did not receive either cash or food assistance.